The Authority of the Pancasila Ideology Development Agency in Providing Recommendations on Laws and Regulations That Are Contrary to Pancasila - Yudha Prasetia Bhakti; Uyan Wiryadi; Teguh Satya Bhakti (Jurnal Mahkamah : Kajian Ilmu Hukum dan Hukum Islam, 2026)
Although Pancasila is recognized as the staatsfundamentalnorm of Indonesia, the legal system has not yet established an institutional mechanism capable of ensuring that legislation consistently reflects its values. This gap creates inconsistency between the normative supremacy of Pancasila and the limited effectiveness of existing supervisory instruments. This study aims to analyze the constitutional position of the Pancasila Ideology Development Agency (BPIP) within the Indonesian state system and to examine the construction of its authority in issuing recommendations on laws and regulations that contradict Pancasila. The research employs a normative juridical method using statutory and conceptual approaches. State institution theory is applied to examine BPIP’s constitutional status, authority theory to assess the scope and limits of its recommendation power, the hierarchy of legal norms theory to explain the relationship between Pancasila and legislation, and political law theory to evaluate the direction of BPIP’s institutional strengthening. The findings indicate that BPIP functions as an auxiliary state organ under the President whose legal legitimacy remains limited because its existence is based solely on a Presidential Regulation. Furthermore, BPIP’s recommendations are non-binding, resulting in juridical implications through the absence of mandatory compliance by lawmakers, political implications through the potential politicization of recommendations, and social implications through differing interpretations of Pancasila values. This study concludes that, de lege ferenda, BPIP should be strengthened through a dedicated law that clearly regulates its constitutional status, authority, institutional relationships, and mechanisms for implementing its recommendations. Such reform is necessary to reinforce Pancasila as the supreme legal norm and ensure greater coherence between constitutional values and the national legislative system.